* På fremmed grund – om degenerationsteorier i dansk kunst og kultur 1880-1945 - Tang Kristensen, Jens (Peripeti, 2018)
With particular focus on prominent Danish medical doctors and psychologists like Frederik Lange (1842-1907), Knud Pontoppidan (1853-1916), Eilert Adam Tscherning (1851-1919) and Carl Jul. Salomonsen (1847-1924) and their definitions of concepts like otherness, dysmorphism and degeneration, this article illustrates how they all had a strong political impact on the avant-garde movements in pre-war Denmark.